Upaya Pengembangan Nilai Agama Dan Moral Dalam Kegiatan Menghafal Do’a-Do’a Pendek Bagi Anak Usia Dini Dengan Penerapan Metode Talaqqi Di Ra Al-Ishlah - Dewi Sinta; Melvi Lesmana; Joni Joni (LPPI Yayasan Almahmudi bin Dahlan, 2024)
The background of this study is the low ability of children in the aspect of religious and moral values, especially in the ability of children to memorize short prayers, The researchers tried to offer a solution to this problem in the form of applying the talaqqi method at RA Al-Ishlah. The type of research conducted is classroom action research which is carried out in 2 cycles with the following stages; planning stage, implementation stage, observation stage and reflection stage. The data collection techniques used are observation and interview, then the data is processed with quantitative and qualitative data analysis techniques. The application of the talaqqi method can determine the weaknesses and strengths of the ability to memorize short prayers. Before the action was taken, the ability to memorize still needed to be improved because there were still many children who could not memorize short prayers such as prayers for riding a vehicle, prayers for both parents, and there were still many sounds letters that were still wrong and incorrect. This is based on an increase in success that occurs continuously where before the action is taken, the child's ability to memorize short prayers only reaches a value of 69.09% with less criteria. After planning and implementing actions in cycle1, the results obtained increased to 94.76% with good criteria. Therefore, the activity of memorizing short prayers with the talaqqi method in learning activities is able to improve children's ability to memorize short prayers at RA Al-Ishlah. Key words: Religious and moral values, memorization activities, talaqqi method